Włoski faszyzm i niemiecki narodowy socjalizm w interpretacji Zygmunta Cybichowskiego do 1939 roku - Marszał, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The subject of the article are the views of Zygmunt Cybichowski (1879–1946), professor of law at the University of Warsaw, on Italian fascism and German National Socialism. This Polish lawyer made a very interesting analysis of totalitarian systems. He was a supporter of the national method of interpreting law. He defined law as a product of the living conditions in a given country, “exclusive” to the solutions adopted in this field in other countries. He argued that the law cannot be invented, but only discovered through the exploration of specific living conditions. In his opinion, not all the law is to be found in the codes, so one should get to know a nation well to discover its laws. Cybichowski, as a supporter of the national-radical movement, looked at the German social and political transformations in the Third Reich with great sympathy. He was impressed by Adolf Hitler.
Keywords: Polish political and legal thought; fascism; Nazism